Wagon Chassis Frame Design with Adaptable Loading Platform - Stastniak, Pavol (Manufacturing Technology Journal, 2015)
The paper present the structural design of freight wagon chassis frame with adaptable loading platform with regard to the safe operation and assessment of the properties by the calculation methods of simulation analysis. 3D model of wagon was created in a computer program PTC/Creo. Wagon chassis frame was subjected to the static and dynamic analysis in programs ANSYS and ADAMS/Rail. On the basis of computer aided simulation analysis was optimized the frame of the wagon. This wagon chassis frame will be able to offer even more capacity and utilize less resources and energy than current wagons for intermodal transport.
Keywords: Freight Wagon; Adaptable Platform; Simulation Analysis